Perencanaan Pengembangan Sarana Prasarana Pendidikan Islam di SD Negeri 01 Talang - Akbar, Hilda Marwani; Melinda, Reza; Rismalinda, Rismalinda; Yusuf, Dodi Muhammad; Asmendri, Asmendri; Sari, Milya (Jurnal Ilmiah Wahana Pendidikan, 2024)
In improving the quality of learning in educational institutions, there are several factors that determine, starting from the curriculum, materials, methods, media, educators, education staff, students, facilities, infrastructure, and so on. This research aims to determine the development of educational facilities and infrastructure at SD Negeri 01 Talang. This type of research is qualitative research. The results of this research indicate that the development of educational facilities and infrastructure at SD Negeri 01 Talang has gone quite well, but there is still some damage and deficiencies in facilities and infrastructure that must be completed by the school. So the results of this research show: (1) Development of educational facilities and infrastructure at SD Negeri 01 Talang, working together to develop educational facilities and infrastructure. (a) Planning for the development of educational facilities and infrastructure. (b) Implementation of development of educational facilities and infrastructure. (c) Supervision of the development of educational facilities and infrastructure. (2) Factors that hinder the development of educational facilities and infrastructure at SD Negeri 01 Talang are that there are several facilities and infrastructure that are not functioning, a lack of learning facilities and infrastructure and a lack of budget for additional facilities and infrastructure.